Individual’s Perception towards Online Shopping in Uttrakhand : A Case Study - Gupta, S. K; Bansal, Anshika (Journal of Commerce and Trade, 2015)
The technology in this digital era is growing with a pace far beyond everyone’s imaginations. New Information Technology have brought about a lot of changes in almost all facets of life. The use of information and communications technologies (ICTs) have changed the way of conducting business transactions and meeting the growing demands of customers for most organizations. The rapid development of the internet has strongly impact upon the worldwide marketing environment. Currently it has become one of the popular approaches for business and customers to perform trade over the internet. The significant growth of online shopping makes the competition in this industry become more intense. Businesses have been coming up with creative ways to promote their product via online. Thus it describes how modern market is replacing the traditional markets. It has become the most efficient way to offer valuable information to the customers like discounts, promotions, new and existing products as per the customer requirements. The objective of this paper is to analyze customer satisfaction level towards online shopping. This paper is descriptive in nature, and data has been collected through various primary and secondary sources. The major findings of the study is that majority of the customers are satisfied.